“This is not my fatherland” Female Genital Mutilation/Cutting in the context of migration: narratives of Nigerian women asylum seekers / “Esta não é a minha pátria”. Mutilação/Corte Genital Feminino no contexto da migração: narrativas de mulheres nigerianas em busca de asilo - Faraca, Annagrazia (Revista Brasileira de Direito, 2016)
Abstract: This paper presents the results of a qualitative research study conducted with nine women asylum seekers from southern Nigeria and residents of the city of Perugia who have undergone the practice of Female Genital Mutilation/Cutting (The common acronym is FGM/C) in Nigeria. The survey explores the migratory and life experiences of these women, and how they live while managing their migratory identities, in order to understand how the migration process affects the system of opinions, attitudes and meanings related to FMG/C as experienced by Nigerian women who were interviewed using a transnational perspective and a gender-sensitive approach. Keywords: Female Genital Mutilation/Cutting; Migration; Trantionalism. Resumo: Este artigo apresenta os resultados de pesquisa qualitativa realizada com nove mulheres solicitantes de asilo do sul da Nigéria e moradoras da cidade de Perugia, que foram submetidas à prática de Mutilação/Corte Genital Feminino na Nigéria. A pesquisa explora as experiências migratórias e de vida dessas mulheres, ao mesmo tempo em que gerenciam suas identidades migratórias, a fim de entender de que maneira o processo de migração afeta o sistema de opiniões, atitudes e significados relacionados à M/CGF como experimentado pelas mulheres nigerianas que foram entrevistadas, numa perspectiva transnacional e numa abordagem sensível ao gênero. Palavras-chave: Mutilação/corte genital feminino; Migração; Transnacionalismo.